2017
DOI: 10.3390/rs9070659
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Sentinel-2A and Landsat 7 and 8 Using Surface Reflectance over Australia

Abstract: Abstract:The new Sentinel-2 Multi Spectral Imager instrument has a set of bands with very similar spectral windows to the main bands of the Landsat Thematic Mapper family of instruments. While these should, in principle, give broadly comparable measurements, any differences are a function not only of the differences in the sensor responses, but also of the spectral characteristics of the target pixels. In order to test for and quantify differences between these sensors, a large set of coincident imagery was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 21 publications
8
68
0
1
Order By: Relevance
“…Previous studies have reported a significant agreement between Sentinel-2 and Landsat-8 data for continuous monitoring of global land surface [35][36][37][38]. However, the combined use of these two sensors or the transition of a model developed with a particular sensor to another, poses a number of challenges due to the difference in the orbital, spatial, and spectral configurations [35].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a significant agreement between Sentinel-2 and Landsat-8 data for continuous monitoring of global land surface [35][36][37][38]. However, the combined use of these two sensors or the transition of a model developed with a particular sensor to another, poses a number of challenges due to the difference in the orbital, spatial, and spectral configurations [35].…”
Section: Introductionmentioning
confidence: 99%
“…Though differences in spatial resolution and spectral bands are key considerations that must be addressed, incorporating Sentinel-2 data would notably improve the temporal repeat time of assessments, providing more opportunities for cloud-free acquisitions [43][44][45]. Enhanced temporal frequency of observations could also improve historic model fitting.…”
Section: Toward An Integrated Disturbance Monitoring Systemmentioning
confidence: 99%
“…The routine use of Sentinel 2A and Sentinel 2B increments the temporal and spatial resolutions providing up to two images per week in the study area with a spatial resolution greater than 100 m 2 (0.01 ha). In addition to this, the compatibility of the NDVI derived from Landsat 8 and Sentinel 2 [36] simplified the calculation procedures. A virtual constellation based on Landsat 8 and Sentinel 2 is being applied during the current campaign of irrigation advice.…”
Section: Discussionmentioning
confidence: 99%